ALIH KODE DAN CAMPUR KODE DALAM PERBINCANGAN ACARA HITAM PUTIH DI TRANS7 - Djago, Meike S. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study aimed to describe the meaning and forms of code switching and code mixing contained in â€œHitam Putihâ€ talkshow, August 2015 edition. The method used in this research is description method. Data analysis used in this research is listening to video talk downloaded through from youtube, researcher liste repeatedly until finding the code switching and code mixing in the conversation with the hosts and guest stars cohost in various themes raised, researcher then write in a notebook and separate code switching from code mixing. From the analysis conducted on Code sourcing and the Code mixing on â€œHitam Putihâ€ talkshow, August 2015 edition, concluded that the exernal transfer code ie rather code that occurred from Indonesian to English in the form of the insertion of words, phrases, and sentences. The form and meaning of the code switching and code mixing in the form of shaped insertion elements; (a) the word, (b) the phrase, (c) or looping reduplications word, (d) idiom or expression, and (e) affixes, such as; prefix + suffix + basic words and basic words. Speech event in the form; (a) setting and scene, (b) participants, (c) end, (d) act sequence, (e) key, (f) instrumentalities, and (g) genre. Â Keywords : Code Switching, Code Mixing, Talkshow, â€œHitam Putihâ€, Trans7.